Continuous opacity monitoring of the growth of bacteria under strict anaerobic conditions. - O'Grady, F (1983)
A newly designed instrument is described which generates continuous records of the opacities of six bacterial cultures growing under strict anaerobic conditions. Additions (for example, of antibacterial agents) or withdrawal of culture (for example, for viable counting) can be made at any time without breach of anaerobiosis. Use of the instrument is illustrated by growth curves obtained from small inocula of two strict anaerobes, Bacteroides asaccharolyticus and Peptostreptococcus anaerobius and by the effects on the growth curve of Bacteroides fragilis of adding various concentrations of metronidazole at different times.